Rancang Bangun Elektronik Motor Relay sebagai Proteksi Berbagai Gangguan Motor Listrik - Resi Dwi Jayanti Kartika Sari; Yahya Chusna Arief; Suryono Suryono (Universitas Merdeka Malang, 2022)
The protection system against disturbances in induction motors has an important role in industry. In general, protection in electrical installations only uses MCB (Miniature Circuit Breaker) and fuses which can only protect against overcurrent and short circuits and there are still many kinds of important protection that have not been covered in it even though along with technological developments many electronic protection devices have been created. The purpose of this final project is to plan and manufacture electronic motor relays against over load, phase loss, phase reverse, phase unbalance, short circuit, ground fault, and locked rotor disturbances. The AVR microcontroller is used as a controller for all systems in detecting disturbances. Where the current setting range and trip time are programmed using the C language which is operated with a keypad and displayed on the LCD. As current and voltage sensing using current transformers and voltage transformers. As for sensing phase reverse, it takes the signal from the differential amplifier and forwards it to zero crossing, trigger and X-or. Testing the accuracy of the electronic motor relay is carried out in each fault. The data obtained shows that the microcontroller can be used as a precision analog voltage controller. This is because the AVR microcontroller has good features and is supported by adequate processor speed for use in this kind of application.